Defining the Sense of Place Components in the Food and Craft Market at the World Heritage Site - Kusumowidagdo, Astrid; Wiradinata, Trianggoro; Rahadiyanti, Melania; Wardhani, Dyah Kusuma; Rembulan, Cicilia Larasati (Bina Nusantara University, 2022)
The research aimed to strengthen the future sense of place by focusing on the sense of place components, namely, physical, social, personal, and shared meaning aspects, as input to local stakeholders. The sense of place of Borobudur Temple stimulated visitors to attend the tourism area at the heritage site, whose potential could be strengthened by promoting the local creative economy and its identity. The research provided theoretical benefits as a basis for further research and practical benefits as input for stakeholders to strengthen the identity of heritage areas. The research was a solution to preserving the historical value of this region in both physical and social aspects in order to strengthen the place’s character as the stalwart of the Borobudur area as a world heritage artifact. The discoveries would clear up the area’s function as Borobudur’s shopping excursion area in a local identity context. Data were collected through structured observation, in-depth online interviews, photos, videos, literature studies, and a manual data analysis procedure. The results show that physical attributes, such as site, build form, and landmark, need improvements. Moreover, social interaction, pedestrian flows, product, personal and shared meanings, comprising history, narration, and event and promotion, should be improved. Further studies should focus on how to improve architecture, modern product variations, and local music. Furthermore, the sense of place will be increased by understanding the services cape of Borobudur Food and Craft Market.